Pregnancy outcomes following different types of bariatric surgery: a national cohort study - Cornthwaite, K; Prajapati, C; Lenguerrand, E; Knight, M; Blencowe, N; Johnson, A; Draycott, T; Siassakos, D (Elsevier, 2021)
OBJECTIVE: To assess the impact of type of bariatric surgery on pregnancy outcomes.